Canonical TSH Regulation of Cathepsin-Mediated Thyroglobulin Processing in the Thyroid Gland of Male Mice Requires Taar1 Expression - Qatato, Maria; Szumska, Joanna; Skripnik, Vladislav; Rijntjes, Eddy; Köhrle, Josef; Brix, Klaudia (Frontiers in Pharmacology, 2018)
Trace amine-associated receptor 1 (Taar1) has been suggested as putative receptor of thyronamines. These are aminergic messengers with potential metabolic and neurological effects countering their contingent precursors, the thyroid hormones. Recently, we found Taar1 to be localized at the primary cilia of rodent thyroid epithelial cells in vitro and in situ. Thus, Taar1 is present in a location of thyroid follicles where it might be involved in regulation of cathepsin-mediated proteolytic processing of thyroglobulin, and consequently thyroid hormone synthesis. In this study, taar1 knock-out male mice (taar1-/-) were therefore used to determine whether Taar1 function would entail differential alterations in thyroid states of young and adult animals. Analyses of blood serum revealed unaltered T4 and T3 concentrations and unaltered T3-over-T4 ratios upon Taar1 deficiency, however, accompanied by elevated TSH concentrations. Interestingly, TSH receptors, typically localized at the basolateral plasma membrane domain of wild type controls, were located at vesicular membranes in thyrocytes of taar1-/- mice. In addition, determination of epithelial extensions in taar1-/- thyroids showed prismatic cells, which might indicate activation states higher than in the wild type. While gross degradation of thyroglobulin was comparable to controls, deregulated thyroglobulin turnover in taar1-/- mice was indicated by luminal accumulation of covalently crosslinked thyroglobulin storage forms. These findings were in line with decreased proteolytic activities of thyroglobulin-solubilizing and -processing proteases, due to upregulated cystatins acting as their endogenous inhibitors in situ. In conclusion, Taar1-deficient mice are hyperthyrotropinemic in the absence of respective signs of primary hypothyroidism such as changes in body weight or thyroid hormone concentrations in blood serum. Thyrocytes of taar1-/- mice are characterized by non-canonical TSH receptor localization in intracellular compartments, which is accompanied by altered thyroglobulin turnover due to a disbalanced proteolytic network. These finding are of significance considering the rising popularity of using TAAR1 agonists or antagonists as neuromodulating pharmacological drugs. Our study highlights the importance of further evaluating potential off-target effects regarding TSH receptor mislocalization and the thyroglobulin processing machinery, which may not only affect the thyroid hormone-generating thyroid gland, but may emanate to other thyroid hormone target organs like the CNS dependent on their proper supply.